Keḷavaṇīnā akhatarā, 1921-1922 : Śrī Dakshiṇāmūrtinī vividha pravrttionuṃ nivedana (SAMP early 20th-century Indian books project, 1922)
On activities of Śrī Dakshiṇāmūrti Vidyārthībhavana in Bhavnagar.